106k views
5 votes
5x + 9 = 2x+7+ 3x - 15​

User Pokiman
by
4.6k points

1 Answer

3 votes

Answer:

x=12

Explanation:

Simplifying

5x + -9 = 3x + 15

Reorder the terms:

-9 + 5x = 3x + 15

Reorder the terms:

-9 + 5x = 15 + 3x

Solving

-9 + 5x = 15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-9 + 5x + -3x = 15 + 3x + -3x

Combine like terms: 5x + -3x = 2x

-9 + 2x = 15 + 3x + -3x

Combine like terms: 3x + -3x = 0

-9 + 2x = 15 + 0

-9 + 2x = 15

Add '9' to each side of the equation.

-9 + 9 + 2x = 15 + 9

Combine like terms: -9 + 9 = 0

0 + 2x = 15 + 9

2x = 15 + 9

Combine like terms: 15 + 9 = 24

2x = 24

Divide each side by '2'.

x = 12

Simplifying

x = 12

User Mumin Ka
by
5.2k points